Experimental study on flash-boiling spray structure of multi-hole gasoline direct injection injector in a constant volume chamber. (July 2020) - Wu, Jian; Du, Jiakun; Chen, Hong; Li, Yuhuai; Zhan, Wenfeng; Wu, Guangquan; Ye, Lin
The macroscopic and microscopic characteristics of flash-boiling spray were experimentally investigated with various optical measurement techniques. The effects of ambient pressure and fuel temperature on flash-boiling characteristics in multi-hole gasoline direct injection injector were analyzed. The analysis was focused on the spray structure and atomization droplet size distributions. In order to increase the understanding of the flash-boiling spray targeting, three injectors with different spray patterns were investigated under strong flash-boiling condition. The results show that ambient pressure and fuel temperature have significant influence on flash boiling. Both lower ambient pressure and higher fuel temperature could accelerate the flash-boiling process. For the macroscopic characteristics, similar influences could be found with the ambient pressure decreased by 0.4 bar and the fuel temperature increased by 10°C. Further, significant difference could be found within cold-jet spray and strong flash-boiling spray, such as the spatial structure. The spray structure always turns from hollow cone into solid when flash boiling occurs. With a higher fuel superheat degree, the spray droplet distribution moves toward smaller sizes and let the larger droplets reduce due to the promotion of atomization. For the strong flash-boiling spray, the Sauter mean diameter has decreased by 50% compared with cold-jet spray. There is a corresponding relationship between collapsed flash-boiling spray target and weighted geometric center of the injector. Spray collapse could be avoided by increasing the plume distance.